2019
DOI: 10.1088/1742-6596/1282/1/012005
|View full text |Cite
|
Sign up to set email alerts
|

Naive Bayes classifier for infant weight prediction of hypertension mother

Abstract: Classification is one method of data analysis in data mining that is used to form a model in order to describe the appropriate data class or model that predicts data trends. The Usage of classification has been applied in various areas, including in health areas. One of the classification methods used is Naive Bayes. This study aims to predict the weight of infants in maternal hypertensive and nonhypertensive conditions with Naive Bayes method. Data were taken as many as 219 data from pregnant women based on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 26 publications
0
11
0
1
Order By: Relevance
“…Linear and non-linear regression analysis for prediction of neonatal weight at birth is presented in 12 . Several such research has been carried out to predict infant weight using probabilistic models 13 , nutritional prediction using artificial intelligence 14 , birth weight prediction using neural network 15,16 , dog body weight prediction using morphological parameters 17 . Other than data mining, image processing-based body weight prediction also proved efficient 18 .…”
Section: Based Body Weight Predictionmentioning
confidence: 99%
“…Linear and non-linear regression analysis for prediction of neonatal weight at birth is presented in 12 . Several such research has been carried out to predict infant weight using probabilistic models 13 , nutritional prediction using artificial intelligence 14 , birth weight prediction using neural network 15,16 , dog body weight prediction using morphological parameters 17 . Other than data mining, image processing-based body weight prediction also proved efficient 18 .…”
Section: Based Body Weight Predictionmentioning
confidence: 99%
“…The data were obtained from 600 pregnant women; however, only 9.5% of the cases were LBW. Desiani et al 1 applied an NB classifier to maternal data for predicting the weight of infants delivered by hypertensive and nonhypertensive mothers. Their dataset included the data of 219 patients from Muhammadiyah Hospital Palembang in Indonesia.…”
Section: Related Workmentioning
confidence: 99%
“…Low BW in infants can occur because of various reasons such as maternal diet, close pregnancy intervals, infections, high parity, preterm delivery, and socioeconomic factors. Compared with normal BW infants, LBW infants are at a higher risk of perinatal death at a ratio of 8:1 1 . Moreover, LBW infants have a greater chance of having serious development problems such as low intelligence quotient (IQ), mental retardation, visual and hearing impairment, neonatal hypothermia, neonatal hypoglycemia, long-term disabilities, and premature death 2 , 3 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 1 summarizes the reviewed literature into 3 categories based on their data size and imbalance issues. The first group of studies used a small data set consisting of <1000 records [ 20 , 21 , 25 , 26 ]. In this group, 50% (2/4) of these studies reported the percentage of LBW cases, which highlights the presence of data imbalance issues [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%